Early initiation of breast feeding and its associated factors among 0-23 months children in Haldwani, District Nainital - Kanubhai, Thakkar Hemaben; Maroof, Mohd; Gaihemlung, Pamei; Maneesh, Bhatt; Kumari, Preeti (Indian Journal of Community Health, 2020)
Introduction: Breastfeeding benefits both the mother and infant. It contains all the essential nutrients in an adequate amount that fulfils the infant first six month’s needs. Early initiation of breastfeeding is necessary to ensure consumption of colostrum having multiple protective factors. Aim and Objectives: To estimate the prevalence of early initiation of breast feeding and to determine its associated factors among 0- 23 months children. Methodology: A community-based cross- sectional study was carried out among 339 children aged 0-23 months in field practice areas of Rural & Urban Health Training Centres (RHTC & UHTC), Department of Community Medicine, Govt. Medical College, Haldwani, District Nainital for a period of 6 months using simple random sampling. Questions related to Early initiation of breast feeding and its associated factors were asked through Epicollect software. Wald’s statistics, Chi- square test, Fisher’s exact test were applied. P value of less than 0.05 was considered as significant. Results: The prevalence of Early Initiation of Breastfeeding was 45.1% (95% CI= 39.9%-50.5%) which was significantly associated with place of delivery, mode of delivery, mother’s education & ANC care. Conclusion: Early Initiation of Breastfeeding practice was found in almost half of children which were significantly associated with various factors highlighting the importance of addressing these factors to improve Early Initiation of Breastfeeding practices.